Effects of students’ mathematics learning strategy and perceived task difficulty on their achievement of mathematics - Woldeab Daniel Eka; Tiruwork Tamiru Tola; Reda Darge Negasi (PLoS ONE, 2025)
This study examined effects of Mathematics learning strategy and perceived-task-difficulty on their achievement. Post-positivism paradigm, quantitative approach and correlations design were employed. Out of 2893 total student population, 351 were sampled using systematic random sampling. Whilst learning strategy and perceived-difficulty were measured using questionnaire, Mathematics achievement was measured teacher-made tests. Pilot study was conducted on 140 samples and the result revealed that Cronbach alpha for both scales appeared above 0.7. The structural equation modeling (SEM) was employed to analyze the data. The path analysis indicated that 22% of variance in mathematics achievement was significantly explained by the joint effects of learning strategy and perceived task difficulty. The result also indicated that the standardized regression weights of (β = .186) and (β = −.374) for learning-strategy and perceived task-difficulty, respectively, were found statistically significant. In conclusion, the effect of Mathematics learning strategy and perceived task difficulty on students’ Mathematics achievement is significant, and positive actions on improving task difficulty and Mathematics learning strategy can enhance Math achievement. Hence, setting tasks with proper level of difficulty and assuring students’ implementation of learning strategy suitable to contents are essential for enhancing students’ achievement in Mathematics.